Pengelolaan Pembelajaran Bahasa Indonesia Pada Program Darmasiswa Di Universitas Muhammadiyah Surakarta - MANSAN, Sulaila; , Prof. Dr. Markhamah, M.Hum; , Dr. Samino, M.M (2015)
ABSTRACT Sulaila Mansan. Q. 100 130 073. Management of Indonesia Language Learning on Darmasiswa Program at Muhammadiyah University of Surakarta. Graduate school. Muhammadiyah University of Surakarta. 2015. The purpose of this study is to describe: (1) Indonesian language acquisition planning for foreign learners on darmasiswa program at UMS. (2) Execution of Indonesian language learning for foreign learners on darmasiswa program at UMS. (3) Evaluation of learning Indonesian language to foreign learners on darmasiswa program at UMS. The method research is a qualitative research and case study research design. Researchers took place in a BIPA class at the Muhammadiyah University of Surakarta. The Techniques of data collection used done by in-depth interviews, observation, and documentation. Data analysis was performed through three stages which are the unity process, data reduction, data presentation, and conclusion. Results of this study are: (1) Indonesian language acquisition planning for foreign learners on darmasiswa program at UMS, the lecturers who teach Indonesian for foreign learners have more experience teaching, with reference to the learning plan drawn up by KUI. (2) Implementation of the Indonesian acquisition to foreign learners on darmasiswa program at UMS, it is conducted by lecturers on three phases of activities, namely initial activity, core activities, and closing activities, and carried out by professors with a variety of learning methods. (3) Indonesian learning Evaluation for foreign learners on darmasiswa program at UMS, carried out in stages in step-by-step from the evaluation of each meeting, the mid-term test evaluation and the end of semester.